2002
DOI: 10.1007/s00467-001-0763-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure after anti-D globulin treatment of idiopathic thrombocytopenic purpura

Abstract: Idiopathic thrombocytopenic purpura (ITP) is a disorder of rapid destruction of antibody-coated platelets. Anti-D immune globulin has been used for treatment of ITP in the United States since 1995. Initial studies identified no significant side effects of treatment. However, a recent report highlighted occasional episodes of intravascular hemolysis after anti-D immune globulin. We describe two children with ITP who developed acute renal failure (ARF) after treatment with anti-D immune globulin and also analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
4
21
0
1
Order By: Relevance
“…However, the etiology of the hemoglobinemia or hemoglobinuria in these patients has not yet been established as "intravascular hemolysis" in terms of immune-mediated or other mechanisms of hemolysis. 3,6,7,10,20,21 Additionally, the laboratory test results generally available for these patients were routine urinalysis results that were consistent with hemoglobinuria and were presumed to represent hemoglobinuria, given the context of acute hemolysis. However, myoglobinuria, which is also consistent with these results, was not ruled out in all patients.…”
Section: Mechanism Of Acute Hemoglobinemia or Hemoglobinuriamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the etiology of the hemoglobinemia or hemoglobinuria in these patients has not yet been established as "intravascular hemolysis" in terms of immune-mediated or other mechanisms of hemolysis. 3,6,7,10,20,21 Additionally, the laboratory test results generally available for these patients were routine urinalysis results that were consistent with hemoglobinuria and were presumed to represent hemoglobinuria, given the context of acute hemolysis. However, myoglobinuria, which is also consistent with these results, was not ruled out in all patients.…”
Section: Mechanism Of Acute Hemoglobinemia or Hemoglobinuriamentioning
confidence: 99%
“…That review suggested that patients receiving anti-D IGIV for ITP or secondary thrombocytopenia be closely monitored for signs and symptoms of those or other potential complications of hemoglobinemia, notably disseminated intravascular coagulation (DIC). Although additional case reports of "acute hemolysis" (or similar terms) following anti-D IGIV administration were subsequently published, [4][5][6][7][8][9][10] no hemolysis-associated complications beyond those described in the 15-patient case series were reported.…”
Section: Introductionmentioning
confidence: 99%
“…If treatment was recommended for the hypothetical patients in the US surveys, there was a striking preference for anti-D in 2001 (from 10% to 33%), reflecting the rapid acceptance of anti-D in the late 1990s. There have been recent case reports of severe, even fatal, hemolysis 32 and renal failure 33 as a complication of anti-D. However, at present the actual frequency of these rare side effects is not known, and the medication has been well tolerated by the great majority of ITP patients.…”
Section: Clinical Management Of Itp In the 21st Centurymentioning
confidence: 99%
“…6 It should also be noted that the diagnostic criteria for IVH in the setting of anti-D treatment are imprecise. Patients not uncommonly experience fever and chills after infusion of IV anti-D, 3 and most cases of marked hemolysis in the authors' experience are due to robust extravascular hemolysis. Moreover, incidental hemoglobinuria may occur in an unexpectedly large proportion of children with ITP, 7 and likely adults, at presentation.…”
mentioning
confidence: 99%
“…Also, IVH may be more prevalent in patients with preexisting hemolysis (eg, Evans syndrome or infection with Epstein-Barr virus) and unusually high levels of residual red cell antibodies from prior treatment. [3][4][5] None of the patients treated in our centers were known to have underlying hemolytic conditions, and we would choose alternative modalities in patients with such findings.…”
mentioning
confidence: 99%